(untitled) (Medical Forum Monthly, 2024)
Objective: To find out how common stunting is among Nawab Shah Sindh's elementary school students Study Design: A Cross sectional study Place and Duration of Study: This study was conducted at the Department of Pediatrics Medicine, university of medical and health sciences for women Nawabshah Sindh from 1st Jan 2024 to 30th March 2024. Methods: A cross-sectional study was conducted with the participation of four government elementary schools in Nawab Shah Sindh. The sample size of 265 was established by using the WHO calculator. The appropriate purposive sampling technique was used. The study was approved by the Ethics Study Committee of the High Institute. Descriptive statistics, namely in the form of percentages and figures, were employed to illustrate the qualitative data. The chi square test was used to find any significant differences between the groups. Results: After increasing significantly with age from the lowest at age 7-8 (grade 2) (9.3%, 4.4%, respectively), the prevalence of overweight and obesity peaked at age 10–12 (grade 4) (P=0.003). Females showed higher rates (12.5%, 8.8%, respectively) compared to boys (9.8%, 7.5%, respectively) (p <0.0001). Offspring of mothers in the high to moderate socioeconomic class and with low to medium levels of education demonstrated a significantly higher risk of overweight and obesity, whereas offspring of mothers in the lower socioeconomic class and with lower levels of education demonstrated a higher rate of thinness. Conclusion: The total percentage of children aged 7 to 15 who are overweight or obese (12%, 9.2%)